2014
DOI: 10.7315/jcde.2014.008
|View full text |Cite
|
Sign up to set email alerts
|

Voronoi diagrams, quasi-triangulations, and beta-complexes for disks in R2: the theory and implementation in BetaConcept

Abstract: Voronoi diagrams are powerful for solving spatial problems among particles and have been used in many disciplines of science and engineering. In particular, the Voronoi diagram of three-dimensional spheres, also called the additively-weighted Voronoi diagram, has proven its powerful capabilities for solving the spatial reasoning problems for the arrangement of atoms in both molecular biology and material sciences. In order to solve application problems, the dual structure, called the quasi-triangulation, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The BetaConcept program is a software designed to understand the concept of geometrical shapes, including Voronoi tessellation, quasi‐triangulation, and others (Kim et al . ). Using the BetaConcept program, we confirmed that most of the chorionic sculptures of A. albopictus eggshells have a typical “hexagon” partitioning surface pattern in accordance with Voronoi tessellation in a two‐dimensional plane.…”
Section: Discussionmentioning
confidence: 97%
“…The BetaConcept program is a software designed to understand the concept of geometrical shapes, including Voronoi tessellation, quasi‐triangulation, and others (Kim et al . ). Using the BetaConcept program, we confirmed that most of the chorionic sculptures of A. albopictus eggshells have a typical “hexagon” partitioning surface pattern in accordance with Voronoi tessellation in a two‐dimensional plane.…”
Section: Discussionmentioning
confidence: 97%
“… Voronoi diagram of 2D circular atoms and its derivative constructs (Figures drawn using BetaConcept ( 27 )). ( A ) The Voronoi diagram (blue lines) of circles and its quasi-triangulation (red lines), ( B ) the β-shape (shaded polygon plus line segments) and corresponding offset (red curve) for a probe of radius β 1 ≥ 0, ( C ) the corresponding β-complex (shaded triangles plus line segments) for β 1 , ( D ) the β-shape (shaded polygon) and the offset (red curve) for β 2 > β 1 , ( E ) the β-complex (shaded triangles) for β 2 and ( F ) the zero β-complex (shaded triangles plus line segments) for a β-probe of zero radius.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1F is called the zero beta-complex corresponding to the probe of zero radius and therefore it contains the intersection information among atoms. Figures 1A - 1F are drawn using BetaConcept ( 27 ). We emphasize that \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\mathcal {BC}$\end{document} and \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\mathcal {BS}$\end{document} for an arbitrary β-value can be computed very efficiently through a binary search of the sorted simplex sets of \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\mathcal {QT}$\end{document} ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1(f) shows an example of \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\mathcal {BC}$\end{document} for β -value. Note that Figure 1 was drawn by BetaConcept ( 38 ).…”
Section: Methodsmentioning
confidence: 99%